2016
DOI: 10.1002/eji.201545465
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal injection of an anti‐Langerin‐HIVGag fusion vaccine targets epidermal Langerhans cells in nonhuman primates and can be tracked in vivo

Abstract: The development of new immunization strategies requires a better understanding of early molecular and cellular events occurring at the site of injection. The skin is particularly rich in immune cells and represents an attractive site for vaccine administration. Here, we specifically targeted vaccine antigens to epidermal Langerhans cells (LCs) using a fusion protein composed of HIV antigens and a monoclonal antibody targeting Langerin. We developed a fluorescence imaging approach to visualize, in vivo, the vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…In this study, LC density observed by in vivo imaging remained unchanged over time, suggesting that in vivo antibody injection, in this experimental setup, did not interfere with LC migration. This is consistent with previous reports showing that the intradermal injection of monoclonal antibodies targeting LCs, in the absence of costimulation signals such as the Toll-Like Receptor Ligand agonist, does not induce LC activation [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, LC density observed by in vivo imaging remained unchanged over time, suggesting that in vivo antibody injection, in this experimental setup, did not interfere with LC migration. This is consistent with previous reports showing that the intradermal injection of monoclonal antibodies targeting LCs, in the absence of costimulation signals such as the Toll-Like Receptor Ligand agonist, does not induce LC activation [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the lack of requirement for adjuvants appeared to depend on helper peptides available in the Ig backbone of the antibody used for targeting, such as motives in the IgG2a backbone in the case of C57BL6 mice 49 . Similarly in non-human primates, an increase of antibody response independently of adjuvant has been observed in the case of antigen targeting to CLEC9A 49 , DCIR 52 , and langerin 53 . No further increase could be obtained with TLR7/8 ligand 53 nor double stranded poly(I:C) 52 , suggesting that a maximal antibody response had been reached or that a key factor was limiting.…”
Section: Discussionmentioning
confidence: 76%
“…Similarly in non-human primates, an increase of antibody response independently of adjuvant has been observed in the case of antigen targeting to CLEC9A 49 , DCIR 52 , and langerin 53 . No further increase could be obtained with TLR7/8 ligand 53 nor double stranded poly(I:C) 52 , suggesting that a maximal antibody response had been reached or that a key factor was limiting. In these cases, the Ig backbone used for targeting may also have played a role and may be involved in the heterogeneity of the responses across individuals.…”
Section: Discussionmentioning
confidence: 76%
“…Different from anti-DC-ASGPR-MOG, the intradermal injection of rhMOG was captured by skin CD1a+CD40+ DC, with pro-inflammatory properties (Salabert et al , 2016). Thus, animals receiving injections of both rhMOG and anti-DC-ASGPR-MOG, likely experienced concomitant priming of MOG-specific effector and regulatory lymphocytes with notorious restraint of otherwise strongly pathogenic autoreactive T cells.…”
Section: Discussionmentioning
confidence: 99%